Television families : is something wrong in suburbia? - Douglas, William, 1949- (LEA's communication series., 2003)
This volume examines television families in the context of family theory and research, and situates TV family analysis in a conceptual framework reflecting the experience of family life. For students and scholars in media studies, family communication and family studies.